Structural phase transition in polycrystalline SnSe: a neutron diffraction study in correlation with thermoelectric properties. Issue 6 (18th November 2016) - Serrano-Sánchez, F.; Nemes, N. M.; Dura, O. J.; Fernandez-Diaz, M. T.; Martínez, J. L.; Alonso, J. A.
Abstract : SnSe undergoes a phase transition immediately below the maximum thermoelectric performance temperature. The present in situ neutron powder diffraction study establishes correlations between the structural evolution and the thermoelectric properties Abstract : SnSe has been recently reported as a promising and highly efficient thermoelectric intermetallic alloy. The present material has been prepared by arc melting, as mechanically robust pellets, consisting of highly oriented polycrystals. The evolution of its orthorhombic GeS‐type structure (space group Pnma ) and phase transition to TlI‐type structure (space group Cmcm ) at high temperature has been studied in situ by neutron powder diffraction (NPD) in the temperature range 295–873 K. This transition has been identified by differential scanning calorimetry measurements, yielding sharp peaks at 795 K. In addition, thermal transport properties were measured in a similar temperature range, and large Seebeck coefficients, as high as 1050 µV K −1 at 625 K, were found. The analysis from NPD data demonstrates an almost perfect stoichiometry, Sn0.998(8) Se, that does not evolve with temperature, and a progressive decrease of the anharmonicity of the chemical bonds upon entering the domain of the Cmcm structure.